The Importance of Fine-Grinding in the Cyanide-Treatment of Gold- and Silver-Ores - FREDERICK C. BROWN (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1906)
THE practice of fine-grinding is now being so successfully - carried on in some fields, notably in West Australia, and its advisability has been so frequently pointed out' that the matter in this paper is not put forward as being new ; its chief object being to call attention to the importance of fine-grinding in the treatment of comparatively low-grade ores. I have been engaged during the last five years in the cyanide-treatment of ores in the Ohinemuri district (North Island), New Zealand, and I consider that, in the near future, extremely fine-grinding (almost sliming) will become a very important feature of the milling-methods in this field, since it seems absolutely necessary to reduce the most of ores to a very fine state of division if a high extraction is to be obtained; and, in most cases, the extra percentage of saving will leave a good margin above the increased cost of treatment due both to the fine-grinding and to the interest on the capital spent for the grinding-machinery. The average ore of the Ohinemuri field is composed of a quartz-gangue with some calcite, carrying the gold-value in the form of an alloy of gold and silver in about equal proportions, and the silver-value in the form of mixed sulphides of silver, usually associated with a considerable amount of iron pyrites. In the upper levels, the ores are decomposed and carry large quantities of black manganese oxide and some iron oxide, but, as. depth is reached, the decomposed ore gives place to sulphides and, in some mines, rhodonite, manganese silicate, is present in fairly large quantities. The average value of the